2011
DOI: 10.1021/jp110372t
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Interfacial Glass Transitions of Water

Abstract: Fast scanning calorimetry (FSC) was employed to investigate glass softening dynamics in bulk-like and ultrathin glassy water films. Bulk-like water samples were prepared by vapor-deposition on the surface of a tungsten filament near 140 K where vapor-deposition results in low enthalpy glassy water films. The vapor-deposition approach was also used to grow multiple nanoscale (approximately 50 nm thick) water films alternated with benzene and methanoic films of similar dimensions. When heated from cryogenic temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
4
23
0
Order By: Relevance
“…Still, our technique cannot distinguish between the existence of one or two fronts, coming from the surface and the interface with the substrate, and thus, our growth rate values can differ up to a factor 2 when compared with those obtained by other techniques which can distinguish the evolution of single fronts. 13 Our front velocities are comparable to previous fast scanning calorimetry measurements from Bhattacharya et al 43 on toluene thin films.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Still, our technique cannot distinguish between the existence of one or two fronts, coming from the surface and the interface with the substrate, and thus, our growth rate values can differ up to a factor 2 when compared with those obtained by other techniques which can distinguish the evolution of single fronts. 13 Our front velocities are comparable to previous fast scanning calorimetry measurements from Bhattacharya et al 43 on toluene thin films.…”
supporting
confidence: 87%
“…In a previous study, Bhattacharya et al found that stable toluene glasses transformed via a front mechanism up to thicknesses of around 2 mm. 43 With our technique, we are limited in film thickness, so it is not possible for us to determine the cross-over length maximum for stable glasses. Even though we do not see variations in the growth front velocity between glasses grown at different deposition temperatures but encoded with the same limiting fictive temperature, we do observe remarkable changes in their cross-over lengths.…”
Section: Effect Of Glass Properties On the Cross-over Lengthmentioning
confidence: 99%
“…500 Ks −1 , was developed by Hager [57] and, even for rates up to 10 7 Ks −1 , by Allen and co-workers [30,58,59]. Similar approaches were used to study the behavior of metastable materials like vapor deposited films [60][61][62][63][64][65]. But, on the other hand, the investigation of metastable phase formation is possible only if the same high-controlled cooling rates are available too.…”
Section: Fast Scanning Calorimetric Techniquesmentioning
confidence: 99%
“…18 Recent single molecular spectroscopy experiments with Rhodamine 700 in hyperquenched glassy water, conducted by Jankowiak and coworkers, 19 indicate that water is not a viscous liquid at temperatures above 140 K, and thus, are in stark contrast to the conclusions of the ESR study. 10 Finally, Bhattacharya et al demonstrated that nanoscale films of amorphous solid water (ASW) show a weak glass transition prior to crystallization, while the bulk-like pure ASW samples do not, 20 which puts in question findings of Souda's group. 6,8,9,21 While recent experimental evidence provides strong support to the notion that water does not undergo a glass transition prior to crystallization, the experimental results which are in contrast with such a view cannot simply be discarded or ignored.…”
Section: Introductionmentioning
confidence: 99%